Battles mentioned in the Holy Quran (before the prophetic mission) - Hiba Abdul Karim Muhammad Al-Hashemi (Islamic Sciences Journal, 2025)
Indeed, the greatest constitution and the most sublime book is the Book of Allah Almighty, which falsehood cannot approach from before it or behind it. It is a revelation from the Wise, the Praiseworthy. The Holy Quran, this sublime book, includes in its contents everything that humanity needs in terms of beliefs, worship, and most of it in dealings and morals. It contains news of the past and those who came before, as well as predictions and what the modern world has revealed of matters that are among its miracles. The Holy Quran includes news of those who came before and the events that occurred between the prophets and nations and their people. I have decided to research the topic: (Battles mentioned in the Holy Quran (before the prophetic mission)) and the reason for choosing this topic is: Because the study of pre-Islamic battles in the Arabian Peninsula faces many problems, the most important of which is the difficulty of chronological and historical control, the mixing of truth with fantasy, in addition to the disparity and disagreement of narrations about historical events, to stand on the details of the battles mentioned in the Quran and to examine them, and to mention the interpretation, biographers, and historians in the causes and results of these battles, and to clarify the most important lessons learned from them and the morals and sermons from that. The research plan included an introduction and four topics: the first topic: Talut and Goliath, the second topic: the battle of Moses with Pharaoh, the third topic: the incident of the elephant, the fourth topic: the battle of the Persians and the Romans, then a conclusion was followed in which the most important results reached by the research were included as well as general result of the study. Send feedback Side panels History Saved.